'Mediterranea massiliensis' gen. nov., sp. nov., a new human-associated bacterium isolated from the right and left colon lavage of a 58-year-old patient. (September 2016) - Mailhe, M.; Ricaboni, D.; Benezech, A.; Saber, K.; Fournier, P.-E.; Raoult, D.
Abstract: We report here the main characteristics of ' Mediterranea massiliensis ' strain Marseille-P2645 T (CSURP2645) that was isolated from stored samples of gut.